Designation of optimal reference strains representing the infant gut bifidobacterial species through a comprehensive multi‐omics approach. (7th October 2022) - Fontana, Federico; Alessandri, Giulia; Tarracchini, Chiara; Bianchi, Massimiliano Giovanni; Rizzo, Sonia Mirjam; Mancabelli, Leonardo; Lugli, Gabriele Andrea; Argentini, Chiara; Vergna, Laura Maria; Anzalone, Rosaria; Longhi, Giulia; Viappiani, Alice; et al.
Abstract: The genomic era has resulted in the generation of a massive amount of genetic data concerning the genomic diversity of bacterial taxa. As a result, the microbiological community is increasingly looking for ways to define reference bacterial strains to perform experiments that are representative of the entire bacterial species. Despite this, there is currently no established approach allowing a reliable identification of reference strains based on a comprehensive genomic, ecological, and functional context. In the current study, we developed a comprehensive multi‐omics approach that will allow the identification of the optimal reference strains using the Bifidobacterium genus as test case. Strain tracking analysis based on 1664 shotgun metagenomics datasets of healthy infant faecal samples were employed to identify bifidobacterial strains suitable for in silico and in vitro analyses. Subsequently, an ad hoc bioinformatic tool was developed to screen local strain collections for the most suitable species‐representative strain alternative. The here presented approach was validated using in vitro trials followed by metagenomics and metatranscriptomics analyses. Altogether, these results demonstrated the validity of the proposed model for reference strain selection, thus allowing improved in silico and in vitro investigations both in terms of cross‐laboratory reproducibility and relevance of research findings.